Al-doping and Properties of AZO Thin Films Grown at Room Temperature: Sputtering Pressure Effect - Chaves, Michel [UNESP]; Ramos, Raul [UNESP]; Martins, Everson [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Cruz, Nilson Cristino da [UNESP]; Durrant, Steven Frederick [UNESP]; Ribeiro Bortoleto, Jose Roberto [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2019)
Aluminum zinc oxide (AZO) thin films were synthesized on glass substrates by radio frequency (rf) magnetron sputtering from a metallic Zn-Al (5 at. %) target at room temperature. The morphological, structural, electrical and optical properties of the films were studied as a function of the sputtering pressure, which was varied from 0.1 to 6.7 Pa. X-ray diffraction (XRD) analyses revealed that the films obtained were polycrystalline, having a hexagonal wurtzite structure with a preferential orientation in the (002) plane. In addition, the crystallite size increased as a function of sputtering pressure. Owing to the re-sputtering of the Zn atoms from the growing film, the aluminum concentration presented a maximum value of 13 at. %. At pressures close to 0.16 Pa, we obtained films with values of electrical resistivity and mobility of 2.8 10(-3) Omega cm and 17 cm(2)/Vs, respectively. Finally, our results indicate that the structure zone diagram proposed by Thornton and later modified by Kluth does not fully predict the structural/morphological behavior of the AZO films, since plasma interactions must also be taken into account. With the methodology used, transparent conductive electrodes can be deposited on substrates at low temperatures.
Keywords: ZnO:Al thin films; TCO; morphological properties; structure zone diagram; room temperature